Description of a new species of Spilomena Shuckard, 1838 (Hymenoptera, Crabronidae: Pemphredoninae) from Western Ghats, India - Puthuvayi Girish Kumar; Sreedharan Amal (Journal of Insect Biodiversity and Systematics, 2025)
Spilomena bobyjosei Girish Kumar & Amal sp. nov., a new species of aphid wasp in the genus Spilomena Shuckard, 1838, is described from the Southern Western Ghats of Kerala, India. This genus is rarely collected from the Indian subcontinent, and most species are described from a single specimen. The genus can be distinguished from closely related genera in having occipital carina absent, hind wing media not diverging before Cu-a, fore wing with marginal cell elongate (longer than stigma), one recurrent vein and two discoidal cells present, stigma large and pronotal collar with complete transverse carina. To date, ten species have been described from India. This paper adds an eleventh species. The differential diagnosis with its nearest species is provided. Additionally, a key to the Indian species of Spilomena is provided.